2021
DOI: 10.1002/celc.202100784
|View full text |Cite
|
Sign up to set email alerts
|

TEMPO‐Mediated Electrochemical N‐demethylation of Opiate Alkaloids

Abstract: A new TEMPO-mediated electrochemical method has been developed for N-demethylation of opiates using a home-made batch cell with low-cost porous glassy carbon electrodes. Ndemethylation of opiates such as thebaine, codeine, morphine and oxycodone is a key step in the semi-synthesis of opioid medicines. The electrochemical N-demethylation using TEMPO as mediator enables the synthesis of noropiates, which is not possible with conventional Shono oxidation. Electrolysis was performed at a preparative scale in aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…A low-cost DC-to-DC electrical converter connected to a solar-powered battery was used to replace the potentiostat by performing gram-scale synthesis of 27c using this system. Divided-cell electrochemical experiments and subsequent LC-MS analysis of anodic and cathodic compartment solutions showed that the reaction only occurs in the anodic cell, supporting the formation of an iminium intermediate as mentioned earlier [ 12 ] ( Figure 17 B). Frazier et al [ 154 ] patented an electrolytic process for glyphosate 90 production.…”
Section: Electrochemical N -Dealkylationsupporting
confidence: 82%
See 3 more Smart Citations
“…A low-cost DC-to-DC electrical converter connected to a solar-powered battery was used to replace the potentiostat by performing gram-scale synthesis of 27c using this system. Divided-cell electrochemical experiments and subsequent LC-MS analysis of anodic and cathodic compartment solutions showed that the reaction only occurs in the anodic cell, supporting the formation of an iminium intermediate as mentioned earlier [ 12 ] ( Figure 17 B). Frazier et al [ 154 ] patented an electrolytic process for glyphosate 90 production.…”
Section: Electrochemical N -Dealkylationsupporting
confidence: 82%
“…Naloxone 8 is an opiate antagonist listed on the Model List of Essential Medicines established by the World Health Organization and is used in life-threatening situations arising from synthetic or natural opiate overdose. Nalbuphine 9 is a mixed opiate agonist-antagonist which is used as analgesic to avoid undesirable effects of morphine [ 11 , 12 ]. The chemical structures of various semi-synthesized opioid medicines are given in Figure 1 (blue box).…”
Section: General Chemical Methods For N -Dealkylat...mentioning
confidence: 99%
See 2 more Smart Citations
“…Beside the importance of the N-dealkylation reaction in the synthesis of drug metabolites, this reaction provides important intermediates for the semi-synthesis of different medicines. [39,40] For example, N-dealkylation of atropine to noratropine is an important step for the semi-synthesis of the bronchodilator ipratropium bromide which is registered in WHO's list of essential medicines. [41,42] Oxidative catalytic N-demethylation of atropine 9 a in the presence of air as oxidant only led to 15 % conversion to 9 b, while using TBHP as oxidant led to 57 % isolated yield.…”
Section: Resultsmentioning
confidence: 99%